Comparative Evaluation of Child Behavior Checklist-Derived Scales in Children Clinically Referred for Emotional and Behavioral Dysregulation - Papachristou, Efstathios; Schulz, Kurt; Newcorn, Jeffrey; Bédard, Anne-Claude V.; Halperin, Jeffrey M.; Frangou, Sophia (Frontiers in Psychiatry, 2016)
Background: We recently developed the Child Behavior Checklist-Mania Scale (CBCL-MS), a novel and short instrument for the assessment of mania-like symptoms in children and adolescents derived from the CBCL item pool and have demonstrated its construct validity and temporal stability in a longitudinal general population sample. Objective: The aim of this study was to evaluate the construct validity of the 19-item CBCL-MS in a clinical sample and to compare its discriminatory ability to that of the 40-item CBCL-Dysregulation Profile (CBCL-DP) and the 34-item CBCL-Externalizing Scale. Methods: The study sample comprised 202 children, aged 7-12 years, diagnosed with DSM-defined Attention Deficit Hyperactivity Disorder (ADHD), Conduct Disorder (CD), Oppositional Defiant Disorder (ODD) and mood and anxiety disorders based on the Diagnostic Interview Schedule for Children. The construct validity of the CBCL-MS was tested by means of a confirmatory factor analysis. Receiver operating characteristics (ROC) curves and logistic regression analyses adjusted for sex and age were used to assess the discriminatory ability relative to that of the (CBCL-DP and the CBCL-Externalizing Scale. Results: The CBCL-MS had excellent construct validity (CFI=0.97; TLI=0.96; RMSEA=0.04). Despite similar overall performance across scales, the clinical-range scores of the CBCL-DP and the CBCL-Externalizing Scale were associated with higher odds for ODD and CD while the clinical range scores for CBCL-MS were associated with higher odds for mood disorders. The overlap amongst the children who scored within the clinical range of each scale was over 90%. Conclusion: CBCL-MS has good construct validity in general population and clinical samples and is therefore suitable for both clinical practice and research.